Industry 4.0: Industrial Revolution of the 21st Century - Popkova, Elena G.; Ragulina, Yulia V.; Bogoviz, Aleksei V. (Studies in Systems, Decision and Control, 2019)
This book addresses a wide range of issues relating to the theoretical substantiation of the necessity of Industry 4.0, the development of the methodological tools for its analysis and evaluation, and practical solutions for effectively managing this process. It particularly focuses on solving the problem of optimizing the development of Industry 4.0 in the context of knowledge economy formation. The book presents the authors' approach to studying the process of Industry 4.0 formation in connection with knowledge economy, and approach that allows the process to be studied in connection with the existing socio-economic and technological conditions. As a result, the conclusions and recommendations could be applied to modern economic systems and do not require any further elaboration. The presented research is based on modern economic theory scientific and methodological tools, including the tools of the theory of economic cycles, the theory of games, and the institutional economic theory. Raising awareness of the problem of Industry 4.0 formation, the book is of interest to a wide audience, including not only specialists and experts with a detailed knowledge of the topic, but also scholars, lecturers, and undergraduates of various fields of economics.